2015
DOI: 10.1149/2.0551510jes
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Highly Conductive Boron-Doped Diamond on TiO2Nanotubes Composite for Supercapacitor or Energy Storage Devices

Abstract: In the present paper, we report the phenomena of the formation of the novel composite nanostructures based on TiO 2 nanotubes (NTs) over-grown by thin boron-doped diamond (BDD) film produced in Microwave Plasma Enhanced Chemical Vapor Deposition (PE MWCVD). The TiO 2 nanotube array overgrown by boron-doped diamond immersed in 0.1 M NaNO 3 can deliver high specific capacitance of 7.46 mF cm −2 . The composite electrodes were characterized by scanning electron microscopy (SEM), Raman spectroscopy, X-ray diffract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 62 publications
2
15
0
Order By: Relevance
“…Based on the proposed deconvolution, the share of the dehydrated NiO in the TiO 2 NTs decorated with NiNPs is around 20%. However, it should be noted that the observed change is not parallel with the modification of TiO 2 chemistry, based on recorded Ti2p spectra ( Figure 4 d), with Ti2p 3/2 peaking at 459.0 eV [ 61 , 62 ]. Finally, the O1s spectra for Ni colloid ( Figure 4 b) reveal the presence of multiple components; therefore, two spectral components were proposed for deconvolution.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the proposed deconvolution, the share of the dehydrated NiO in the TiO 2 NTs decorated with NiNPs is around 20%. However, it should be noted that the observed change is not parallel with the modification of TiO 2 chemistry, based on recorded Ti2p spectra ( Figure 4 d), with Ti2p 3/2 peaking at 459.0 eV [ 61 , 62 ]. Finally, the O1s spectra for Ni colloid ( Figure 4 b) reveal the presence of multiple components; therefore, two spectral components were proposed for deconvolution.…”
Section: Resultsmentioning
confidence: 99%
“…The active surface area of TiO 2 NT/BDD‐10k was 1062 cm 2 . The detailed studies on the origin of the enhanced electrochemical activity of fabricated titania‐based diamond composites showed that such promising capacitive properties could be attributed to two main factors. The first concerns the specific architecture of TiO 2 NT, which provides a high real surface area and straight path for charge percolation, whereas the second is related to the modification of the titania structure induced by BDD coverage during the microwave plasma enhanced chemical vapor deposition (MWPE‐CVD) process involving: partial transformation from anatase to the rutile phase, Ti−C bonding that improves integration between titania and BDD, and the appearance of Ti 3+ , which affects the sample conductivity.…”
Section: Diamond‐based Compositesmentioning
confidence: 99%
“…Titania nanotubes (TiO 2 NT) modified by boron‐doped diamond is a promising candidate for the fabrication of supercapacitors . On the contrary to Shi et al., the highly ordered layer of titania (8 μm in length and 30 nm in internal diameter) was produced by anodization of a Ti metal plate serving as a substrate for BDD growth (Figure A) during the CVD process with different diborane concentrations in the gas phase (B/C ratio equals 2000, 5000, and 10 000).…”
Section: Diamond‐based Compositesmentioning
confidence: 99%
See 2 more Smart Citations